MONITORING OF GROUNDWATER QUALITY CHANGES IN IRRIGATED LANDS OF KASHKADARYA REGION (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, a comprehensive study of changes in the quality of groundwater in the irrigated lands of Kashkadarya region is conducted, with the main focus on the impact of cotton cultivation. During the research, changes in the groundwater level and salinity were monitored in Karshi, Qamashi and Kitab districts. Modern monitoring equipment, including an online monitoring system (Diver), has been launched for continuous data collection. The analysis reveals important insights into the condition of reclamation wells and the overall quality of groundwater in the region. It should be recognized that the water resources of Kashkadarya region are very unevenly distributed. The lack of water resources is certainly observed a lot at the district level, and their quality indicators are very important. In the article, the quality indicators of underground water in the irrigated lands of Kashkadarya region on the scale of districts, the quality indicators of underground water are determined based on the data obtained from observation wells. Groundwater was studied in a cross-sectional area and monitored in the example of Qamashi, Karshi, Kitab districts. Monitoring analysis of the surface water level indicators was carried out on the general areas, and in 45.47% of the areas, the surface water level corresponds to the range from 3 to 5 meters.